BENTUK-BENTUK GAYA BAHASA SATIRE DALAM MONOLOG AWAL ACARA TELEVISI MEET LIVE METRO TV - Rince Novalika; Meddyan Heriadi; Asmara Yumarni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
satirical language styles in television media as a means of social and political criticism packaged through humor, irony, and satire. The opening monologue of the Meet Live Metro TV program is interesting to study because it contains various criticisms of social and political phenomena developing in society. This study aims to describe the forms of satirical language styles used in the opening monologue of the Meet Live Metro TV program and analyze the relationship between satirical speech and the social and political realities that are the targets of criticism. The study uses a qualitative approach with a descriptive method. The data are in the form of speech in the opening monologue of several Meet Live Metro TV episodes that contain satirical elements. Data were collected through observation, documentation, listening, and note-taking techniques, then analyzed using Northrop Frye's satire theory through the stages of data reduction, data presentation, and drawing conclusions. The results show that the opening monologue of the program utilizes various forms of satirical language styles, namely ironic satire, sarcasm satire, parody satire, hyperbolic satire, cynicism satire, and socio-political satire. The most dominant form of satire is used to criticize government policies, corruption, social inequality, infrastructure, and various other public issues. Furthermore, it was found that satirical discourse has a strong connection to current social and political realities in society. Through humor and satire, criticism is delivered in a more engaging and easily accepted manner by viewers. Thus, the opening monologue of Meet Live Metro TV serves not only as entertainment but also as a medium for social criticism that can raise public awareness and critical thinking. Keywords: style, satire, opening monologue, social criticism, Meet Live Metro TV.